Artificial fertilization: the ethical problems - Sgreccia, Elio (Medicina e Morale, 1993)
The rapid development of the reproductive technologies has caused many problems of ethical nature (medical-ethical, ethical-legal, ethical-economic). But the main ethical questions are about: the suppression and/or manipulation of embryonic life during or because of reproductive technologies; the separation between being married and being parents within marriage and the family; the division between the two dimensions (unitive and procreative) of the intercourse. In the light of the Catholic teaching on the theme, a teaching that is particularly clear in the document Donum Vitae, the Author provides the way to distinguish the techniques that respect the dignity of the human embryo and the integrity of the intercourse and that of the institution of the family.